Internet Usage and Academic Performance: An Empirical Study of Secondary School Students in Kashmir - Mir, SA; Paray, AA (International Journal of Computer Sciences and Engineering, 2025)
The present investigation was carried out to study the academic achievement of secondary school students with respect to gender and type of school. A sample of 240 secondary school students (120 male and 120 female) was drawn randomly from two districts (Anantnag and Kupwara) of Kashmir (J&K), India. Self-constructed Information Blank was used to locate the Internet-user secondary school students. The subjects’ previous academic marks secured in their final examination conducted by J&K BOSE have been taken a major yard-stick to assess the academicperformance. The data was subjected to statistical analysis by applying mean, standard deviation and t-test. A significant difference between male Internet-user and female Internet-user secondary school students was confirmed. The results further highlighted a significant difference on academic performance of internet users with respect to their type of school.